Studi Inovasi dan Praktik Akad Ganda Sistem Keuangan Islam Tradisional Berbasis Fatwa Ulama Lokal - Muhammad Djakfar; Umrotul Khasanah; Meldona Meldona (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2019)
Food production financing is expensive because facility inputs controlled by Trans-National Corporation (TNC), and output is conducted by traders using the bonded system. This condition leaves farmers in a dilemma position so that farmers make innovations and practice multiple contracts in the traditional Islamic financial system based on the fatwa of local ulama. The purpose of this study is to uncover the views of farmers, disclose opinions or views of ulama, and reveal the model of financing applications based on traditional Islamic financial systems and the application of dual contracts that apply in the farming community. This research puts forward a descriptive qualitative research method with case studies on farmers in Probolinggo Regency and Malang Regency, East Java. This research model uses qualitative methods that are concerned with the meaning, context and emic perspective. Data analysis through a phased approach, namely: analyzing important statements, formulating, describing, reducing data to the findings, propositions and conclusions. Data collection and analysis carried out simultaneously; prioritize observations and interviews and the researcher himself as the main instrument. The research findings show that farmers in Probolinggo Regency and Malang Regency, East Java Province have innovated and practised a dual agreement in the traditional Islamic financial system based on the fatwa of local ulama. The motive of the farmers to do the work is to avoid the practice of usury which is prohibited. The results showed that there were four traditional Islamic financial models practiced by farmers, namely: (1) the leasing model, (2) the buying and selling model "binding" with the usual profit sharing, (3) the buying and selling model "binding" with the profit-sharing half and (4) buying and selling model "binding" with profit-sharing.Keywords: Dual Agreement, Financing, Islamic Financial Model, views of ulama, farmers